(untitled) (Vietnam Journal of Community Medicine, 2023)
Background: Analysis to evaluate occlusal changes is very important in assessing orthopedic treatment outcomes. There are many analytical methods based on measurements on plaster samples before and after treatment, such as measuring the distance between teeth and width of jaw arch or based on an occlusal index such as ICON, PAR index. Objectives: Evaluation of the change in PAR index (peer assessment rate) after treatment of Class II Angle malocclusion with the MBT bracket system at the Department of Odonto-Stomatology, Can Tho University of Medicine and Pharmacy. Materials and methods: The study was conducted on 31 patients with Class II Angle malocclusion at the Department of Odonto-Stomatology, Can Tho University of Medicine and Pharmacy. The patients were treated for orthodontic treatment of Class II Angle malocclusion. Evaluation of treatment results according to PAR. Degree of change = PAR before treatment - PAR after treatment Result: The PAR index (W) before treatment was 32.19 ± 13.84. Among the components of the PAR index (W), overbite has the highest score of 11.16 ± 8.12, and overbite has the lowest score of 2.00 ± 1.55. The index that changed the most was the overbite, reduced by 10.65 points, improved by 93.67% after treatment, and the crowding in the posterior teeth decreased by at least 0.65 points, improved by 40.89%. Conclusion: In the of PAR(W) after treatment, the occlusal components all had a great change after treatment, there was no component in the coefficient that did not improve, indicating that the occlusion is very well improved, good guarantee in terms of functionality and stability.